From Da'wah Management to Prophetic Management: Efforts to Reconstruct the Epistemology of Da'wah Management Based on Humanization, Liberation, and Transcendence - Siti Fatimah; Maryono (Indonesian Journal of Da'wah Management Scholars, 2026)
Background of the study: Da'wah Management has developed primarily in a technical-administrative manner with weak epistemological foundations, reducing da'wah to managerial activities and obscuring its role as a praxis of social transformation. Aims and scope of paper: This article aims to reconstruct the epistemology of Da'wah Management toward a Prophetic Management paradigm grounded in humanization, liberation, and transcendence, with a focus on the development of Islamic higher education as a scientific and institutional field. Methods: This study employs a qualitative, conceptual-epistemological approach using a critical literature review to examine the scientific foundations of Da'wah Management and formulate an alternative paradigm. Result: The findings reveal the dominance of positivistic-technocratic and normative-fiqh epistemologies that reduce da'wah to administrative skills, and propose prophetic epistemology as an alternative framework that is humanistic, emancipatory, and transcendental. Conclusion: The Prophetic Management–based reconstruction positions Da'wah Management as a transformative socio-religious discipline, with implications for redefining institutional roles, curriculum design, and graduate profiles as prophetic leaders responsive to contemporary humanitarian challenges.